MÖNCH detector enables fast and low-dose free-propagation phase-contrast computed tomography of in situ mouse lungs - Dullin, Christian (Journal of synchrotron radiation, 2018)
Due to the complexity of the underlying pathomechanism, in vivo mouse lung-disease models continue to be of great importance in preclinical respiratory research. Longitudinal studies following the cause of a disease or evaluating treatment efficacy are of particular interest but challenging due to the small size of the mouse lung and the fast breathing rate. Synchrotron-based in-line phase-contrast computed tomography imaging has been successfully applied in lung research in various applications, but mostly at dose levels that forbid longitudinal in vivo studies. Here, the novel charge-integrating hybrid detector MÖNCH is presented, which enables imaging of mouse lungs at a pixel size of 25 µm, in less than 10 s and with an entrance dose of about 70 mGy, which therefore will allow longitudinal lung disease studies to be performed in mouse models